2014
DOI: 10.1002/lary.24887
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of vocal dosimetry for assessing voice rest

Abstract: Objective Voice rest is frequently recommended following surgical disruption of vocal fold epithelium, but patients report variable adherence to voice rest recommendations. The objective of this study was to assess the clinical utility of an ambulatory vocal dosimeter for measuring adherence to voice rest recommendations. Study Design Outcomes research Methods Part 1: To determine the utility of the dosimeter in non-clinical use, the relationship between self-reported voice use and dosimeter measurements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…Previous studies have shown that subjects are typically tolerant of wearing a vocal dosimeter such as the Vocalog for prolonged periods of time . A feasibility study looked at employing the Vocalog device as a measure of gauging patient compliance following vocal cord surgery . This study with 11 patients showed the voice dosimeter was an effective means of measuring compliance to postoperative voice rest prescription …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that subjects are typically tolerant of wearing a vocal dosimeter such as the Vocalog for prolonged periods of time . A feasibility study looked at employing the Vocalog device as a measure of gauging patient compliance following vocal cord surgery . This study with 11 patients showed the voice dosimeter was an effective means of measuring compliance to postoperative voice rest prescription …”
Section: Discussionmentioning
confidence: 99%
“…A feasibility study looked at employing the Vocalog device as a measure of gauging patient compliance following vocal cord surgery . This study with 11 patients showed the voice dosimeter was an effective means of measuring compliance to postoperative voice rest prescription …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 This instrument is marketed as Ambulatory Phonation Analyzer and has been used rather extensively to study the voice use in student singers 19 ; monitoring and logging voice use in call center operators, 20 teachers, 21 after surgery 22 ; and for clinical use with patients with voice disorders. 18 With the attachment of the accelerometer to the neck above the sternal notch, the accelerometer detects the skin vibration during phonation.…”
Section: Introductionmentioning
confidence: 99%
“…Of direct relevance to the current study, Ohlsson, Brink, and Löfqvist (1989) reported large discrepancies between self-reported speaking time (62%-71%) and phonation time derived from a contact-microphone-based ambulatory voice monitor (5%-7%); in that study, however, only speakers with normal voices were monitored, and a quantitative statistical analysis between self-reported and voice-monitor data was not carried out. In more recent work, Misono, Banks, Gaillard, Goding, and Yueh (2015) report that phonation times measured with a VocaLog (Griffin Laboratories, Temecula, CA) voice dosimeter correlated moderately (r = .62) with self-reported estimates of voice use by subjects with normal voices. However, subjects were monitored for only 2 hr, and there is some evidence that the VocaLog tends to overestimate phonation times (Van Stan, Gustafsson, Schalling, & Hillman, 2014).…”
mentioning
confidence: 98%